Utility of Red Tide (Karenia brevis) Monitoring Data as a Predictive Tool to Estimate Brevetoxin Accumulation in Live, Free-Ranging Marine Mammals - Fire, Spencer E.; Miller, Glenn A.; Sabater, Edna R.; Wells, Randall S. (Frontiers in Marine Science, 2021)
Exposure of common bottlenose dolphins (Tursiops truncatus) to brevetoxins (PbTx) produced by blooms of the toxic phytoplankton Karenia brevis frequently results in severe health impacts, including illness and large-scale mortality events. Although PbTx accumulation in dead-stranded dolphins is well documented, there are limited data for corresponding brevetoxin exposure in live dolphins. In addition, the severity of impacts on living survivors of such toxic blooms is difficult to assess due to a lack of data on the relationship between K. brevis bloom severity and corresponding PbTx concentrations in exposed animals. Here we present results of PbTx analysis of urine, serum, milk, gastric fluid, and feces samples collected from live, free-ranging dolphins (n = 253) from Sarasota Bay, Florida during 2000–2018, and investigate the relationship between PbTx concentrations detected and corresponding K. brevis cell abundances that are temporally (within 30 days) and spatially (within 16 km) associated with each individual. We found that 28% of dolphins were associated with elevated K. brevis abundances (10,000–60,000,000 cells/L), with 41% (n = 104) of dolphins testing positive for PbTx in at least one sample type. The proportion of PbTx-positive animals was significantly greater in animals exposed to elevated cell abundances vs. those exposed to background cell abundances (<10,000 cells/L), with 60 and 34% testing positive, respectively (p < 0.001). PbTx was detected most frequently in feces (57%, n = 38), followed by gastric (35%, n = 37), urine (32%, n = 55), and blood (7%, n = 17). PbTx concentrations by sample type were highest in feces (2–231 ng/g; mean 46), followed by urine (0.8–90 ng/g; mean 7.2), gastric (0.8–61 ng/g; mean 12), and blood (0.3–5 ng/g; mean 1.3). Regression analyses of K. brevis cell abundance as an index of exposure vs. corresponding PbTx concentration found no statistically significant relationship for feces (p = 0.120), gastric (p = 0.349), urine (p = 0.053), or blood (p = 0.729) samples. PbTx concentrations typically ranged over two orders of magnitude between minimum and maximum values and did not scale with corresponding indices of exposure, which ranged over three orders of magnitude or more. Our results indicate that K. brevis cell abundance alone is a poor predictor of brevetoxin accumulation in bottlenose dolphins, and suggest that alternative methods (e.g., endocrine or immunological biomarkers) should be investigated as more appropriate methods for determining the severity of health impacts due to red tides.